The influence of stromal fibroblast on antigen-presenting cell function and alteration of their biology - Mohammad, Salaheddin (2022)
Dendritic cells (DC) and macrophages (Mɸ) are antigen presenting cells (APC) that orchestrate immune activation, immune and tissue homeostasis, and disease pathology. In the case of Mɸ that act in tissue repair and wound healing, it is important that local inflammation is tightly controlled. Disorder in inflammatory processes leads to impaired regeneration, excessive remodelling or immune suppression. In contrast, the major functions of DCs include priming and tolerization of immune responses, disruption of which has major impact on responses to infectious disease, malignancy, or can result in autoimmunity. Whilst a sizeable body of research has studied DCs and Mɸ, there has been relatively little attention paid to the role of stromal cells that share their tissue microenvironment.